Pemberdayaan Remaja dengan Program Kelas “Melek” Status Gizi di Sekolah Z Limo, Depok - Simanungkalit, Sintha F; Lumban Tobing, Duma; Wahyuningsih, Utami; Simanjorang, Chandrayani (Poltekita: Jurnal Pengabdian Masyarakat, 2024)
Body image is a perception of how someone sees and thinks about their body. Teenagers are more interested in their body shape and this will have an impact on their self-confidence. Teenagers' dissatisfaction with their bodies can encourage them to adopt the wrong diet in an effort to get the ideal body shape. Body image is one of the factors that influences nutritional status. Teenagers tend to easily experience stress which may be caused by problems at school or in their friendship environment. In-depth knowledge is needed so that teenagers can manage their stress well. Based on reports from School Z, around 100% of teenagers have never received counseling regarding nutritional status and stress management. This activity aims to provide students with in-depth knowledge and understanding regarding body image and stress management. The counseling was carried out in August 2023 and involved class 10 students at Z High School as the main target. Counseling is delivered through PowerPoint, leaflets and posters. The students fill in the pre-test and post-test questions to be used as evaluation material for this activity. There is an increase in the minimum knowledge score, namely 0 (zero) during the pre-test to 60 during the post-test. The community service team hopes that after the activities take place, teenagers will be able to independently monitor nutritional status and manage stress.